Proper Software Engineering Process in Developing an Integrated Telehealth System - Khanapi Abd Ghani, Mohd; Musa Jaber, Mustafa; A Mostafa, Salama; Mustapha, Aida; Abed Mohamed, Mazin; Aman, Hannani (International Journal of Engineering and Technology, 2018)
Software development project becomes difficult because of the complexity in the business requirements, rigid framework and unpredictable performance. These cause difficulties to deliver the software on time, to maintain it and to adapt to new requirements. These scenarios had been faced in developing the healthcare information system which typically complex and comprehensive. Due to its complexities, the development of healthcare information system and other related healthcare applications typically disparate and less integrated.Â  This led to maintenance and system integration issues that recently struggling by most healthcare providers around the world to resolve it by putting effort to link all existing disparate system into integrated one. This was due to the fact that a proper software engineering process was given less attention at the beginning of the health ICT project. This paper proposed, a systematic software engineering process based on customized Rational Unified Process for managing the development of integrated telehealth system. This paper also proposed literate modeling approach for performing system analysis and design model for usersâ€™ accessibility and comprehensibility.Â